Gangguan Saluran Transmisi di Deteksi Menggunakan Metode Gelombang Berjalan dan Transformasi Wavelet Diskrit - Seftiani, Yudia Meka; Novizon, Novizon; Ari Fitra, A. (Teknik Elektro Politeknik Negeri Padang, 2023)
Determination of fault location using impedance-based methods and the traveling wave method. Many previous studies used the impedance method but found deficiencies; if the fault impedance is high, it affects the accuracy of determining the fault location. Another method uses the global positioning system (GPS), which is less economical because it requires a lot of expensive devices. This research focuses on the traveling wave method popularized by Bewley, which uses high-frequency electromagnetic impulses derived from transient voltage and current faults inside and outside the line. This method ignores the fault type, line resistance, and fault start angle. In analyzing the time difference between the incident and reflected waves, a discrete wavelet transform analysis is used to help determine the location of the disturbance. The Maninjau hydroelectric power plant and the Pauh Limo substation are modeled using an alternative transient program (ATP) with several components and parameters. Modeling is given for one-phase ground disturbance, two-phase ground disturbance, two-phase, three-phase, and lightning surge. Determination of fault locations using single-ended and double-ended methods with a sampling rate of 1 Mhz by varying the type of wavelet (Daubechies 4, Coiflets 4, Symlets 4) The results obtained in determining the location of disturbances based on the type of wavelet, Daubechies 4, have a small error, so the accuracy is high, and the method double ends for all types of interference to obtain a smaller error rate.